Electromagnetic grazing anomalies. Energy flux extrema - Kats, A.V. (Физика низких температур, 2019)
The diffraction of electromagnetic waves at the surface periodic structures accompanied by strong anomalous effects in different diffraction orders is considered in detail for high-contrast interfaces. We restrict discussion by the transverse magnetic polarization of the incident wave (the magnetic field is orthogonal to the plane of incidence) and the simplest geometry when the plane of incidence is orthogonal to the grating grooves. The most attention is devoted to the strong maxima and minima of the energy flux density accompanying specific grazing propagation of some diffraction order. Relation to other anomalies, both Rayleigh and the resonance ones is discussed as well. Ретельно проаналізовано дифракцію електромагнітних хвиль на поверхнях з періодичними структурами, що супроводжується великими аномальними ефектами. Розглянуто межі поділу середовищ з високим контрастом властивостей. Дослідження обмежено випадком ТМ поляризації хвилі, що падає на межу (магнітне поле перпендикулярне до площини падіння), та найпростішою геометрією, коли площина падіння ортогональна до штрихів гратки. Найбільшу увагу приділено максимам та мінімумам густини потока енергії, що супроводжують ковзне розповсюдження в деякому дифракційному порядку. Обговорюється зв’язок з іншими аномаліями, як релеївськими, так і резонансними. Детально проанализирована дифракция электромагнитных волн на поверхностях с периодическими структурами, сопровождаемая сильными аномальными эффектами. Рассматриваются границы раздела сред, отличающихся высоким контрастом свойств. Исследование ограничено случаем ТМ поляризации падающей на границу волны (магнитное поле ортогонально плоскости падения) и простейшей геометрией, когда плоскость падения ортогональна штрихам решетки. Наибольшее внимание уделено максимумам и минимумам плотности потока энергии, сопровождающими скользящее распространение в некотором дифракционном порядке. Обсуждается связь с другими аномалиями, как рэлеевскими, так и резонансными.